Polarization of Journalists' Attitudes Regarding State Bonds to Press Freedom and Media Continuity - Hendriana , Yadi Heriadi; Hidayat, Dadang Rahmat; Rusmana, Agus; Sjafirah, Nurya Asri (Journal of Ecohumanism, 2024)
The COVID-19 pandemic precipitated a myriad of alterations and substantial repercussions across numerous domains of human existence. Beyond merely affecting the healthcare sector, COVID-19 has also exerted influence over the sustainability of educational systems, economic structures, public governance, and even the journalistic field. These circumstances have led to a notable decline in advertising revenues within the media, necessitating reductions in employee wages, implementation of layoffs, and in some instances, declarations of insolvency. A strategic governmental intervention designed to mitigate the economic ramifications of the pandemic on the press has been the establishment of collaborative initiatives between governmental bodies and media organizations, which includes the provision of financial assistance. Although these initiatives are ostensibly intended to bolster the media sector, they have subsequently manifested as a potential jeopardy to the autonomy of the press. Employing qualitative methodologies grounded in critical paradigms, the research undertook an analysis of both primary and secondary data, acquired through comprehensive interviews with journalists and stakeholders in media policy, alongside extensive desk research utilizing diverse documentary sources. The findings of the investigation indicated that the collaboration between the case study television station and the Indonesian government during the pandemic, while yielding benefits for both entities, engendered a power dynamic that compromised the independence of the media in the context of the pandemic.